Penerapan Telemedicine terhadap Penyembuhan Luka Kaki Diabetik Grade IV Paska Amputasi - Nila Indrayati; Debie Dahlia; Riri Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the healing process of diabetic foot wounds monitored through telemedicine during the Coronavirus disease-19 pandemic. The method used in this study was a case report of a 64-year-old patient with a history of grade IV diabetic foot injuries after amputation of the thumb on the right foot. The time needed to do telemedicine as a medium for monitoring wound conditions and education is about 30 minutes. The results showed that wound healing was significantly successful, within one month, as many as ten dressing changes with a duration of once every three days. In conclusion, telemedicine contributes positively to efforts to heal diabetic foot wounds. Keywords: Case Report, COVID-19, Diabetic Foot Sores, Telemedicine